Penetrating craniocerebral injury with nails: Case report - Bhaganagare, Amresh; Nadkarni, Trimurti; Goel, Atul (Indian Journal of Neurotrauma, 2007)
A 19 year-old-male presented with three nails being hammered into his head. The patient had no neurological deficits at the time of presentation. Computed tomography (CT) of the brain showed the nails to have penetrated both tables of the skull. All of these metallic foreign bodies were extracted surgically. One of these nails, noted in the midline, was bent at its shaft and lay in the epidural space. The other two nails lying parasagittally had penetrated into the brain parenchyma of the frontal lobes. There was no intraparenchymal hemorrhage noted in relation to the tracts of the nails. The patient had an uneventful postoperative recovery. The relevant literature related to this unusual case is reviewed.
Keywords: craniocerebral injury; nails; penetrating injury